Local Wisdom Practices In Preserving Multiculturalism In The East Amanuban Community, South Middle East District Of Indonesia - Arsyad, Abdul Rahman (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Religious disagreements frequently lead to conflicts and divide in society. A minor portion of the issues that arose in East Amanuban is the case of certain individuals rejecting Muslim places of worship. The goal of this study is to make clear how local knowledge can be applied to problem-solving. According to the research findings, when building Islamic halls of worship, local wisdom can reconcile problems between Islam and Christianity. The first reason that Christian groups opposed building Muslim halls of worship was because they were suspicious of the Islamization efforts made by Muslim communities. Talk between religious leaders, the government, and traditional wisdom practices is given priority in conflict resolution. The term Oko Mama is used to symbolize unification. Because the king’s Amanuban Kingdom fairly divided its people to adopt Christianity and Catholicism in the past and because intermarriage occurred during the spread of Islam, local wisdom is strong. Their interaction with each other is the foundation for fostering harmony without recognizing distinctions; for the locals, they are brothers who preserve the principles of indigenous wisdom. Even when family members hold different ideas, the custom of local knowledge placing a higher value on religion is a private matter that shouldn’t be tampered with. Because of this, the local knowledge of the East Amanuban community has preserved multiculturalism in the face of information and technology disruption, which frequently results in the disruption and even the fading of the values of variety in contemporary society’s social interactions.